Pemanfaatan Limbah Kulit Pisang Sebagai Pupuk Organik Cair dan Aplikasinya Terhadap Pertumbuhan Tanaman Kangkung Darat (Ipomea Reptans Poir) - Manis, Ince; Supriadi, Supriadi; Said, Irwan (Universitas Tadulako, 2017)
Banana peel waste utilization as organic manure and its application has been made to the land kale plant growth (Ipomea reptans Poir). This paper aims to describe how to manufacture liquid organic fertilizer from the waste banana skin, determine the total nitrogen content of liquid organic fertilizer and the effect of liquid organic fertilizer waste banana skin on plant growth kale land (Ipomea reptans Poir). The method used was experimental at the stage of making a liquid organic fertilizer waste banana peel in fermentation, the determination of total nitrogen content and the application of the organic liquid fertilizer waste banana skin using a randomized block design (RBD) with 4 treatments include P0 (0 mL); P1 (20 mL); P2 (40 mL); and P3 (60 mL).The parameters measured were plant height (cm), the number of leaves (leaf) and wet weight (g). The growth data of the swamp cabbage land (Ipomea reptans poir) were analyzed by using the statistical test analysis of variance (ANOVA) then followed by Duncan test with significance level of 5%. The results showed that levels of total nitrogen of the organic liquid fertilizer waste was 0.032% and the application of the organic liquid fertilizer of banana peel waste on the growth of swamp cabbange land (Ipomea reptans poir) influence on plant height (cm) and wet weight (g) but have no effect on the number of leaves (leaf). Treatment P2 (40 mL) showed the best result for the average plant height (cm), the number of leaves (leaf) and wet weight (g) of the swamp cabbage land (Ipomea reptans poir).